Cupping as a Special Therapy for Health Services in Tourist Attractions: Literature Review - Dwi Indah Lestari; Siti Riskika; Alwan Revai; Destia Widyarani (D'Nursing and Health Journal (DNHJ), 2022)
Introduction: Cupping is one of the traditional health therapies that has existed in the world since 1550 BC in the ancient Egyptian era, based on Riskesdas data in 2018 it was found that 31.4% of people in Indonesia used traditional health services including cupping in it, although medically there have not been many studies that explain about the benefits of cupping against certain diseases. Method: Search articles via Science Direct, PubMed and Google Schoolar, search year restricted from 2014-2020. Result: There were 11 journals found from 9,864, this literature review generally recommended the provision of traditional cupping therapy for the community while still paying attention to safety, sterility and security in performing the given cupping action. Conclusion: cupping can be done in tourist spots to help tourists who may experience aches or to provide healing and feel a comfortable sensation in cupping, cupping options at tourist attractions.